SPORT SPONSORSHIP ACTIVATION FOR CUSTOMER ENGAGEMENT AND ITS IMPACT ON BRAND STRENGHT AND BRAND EQUITY THROUGH SOCIAL MEDIA - Σαρλή, Ελένη (Πανεπιστήμιο Πελοποννήσου, 2024)
New technology has allowed business to discover new ways of managing what is, to them, the most profitable factor of production: their customers. Their management has become a major factor for them, creating the need for their management systems. This need has been met by Customer Relationship Management Systems. Specifically, they helped businesses sort, prioritize, and manage customers in the best possible way, giving each one the same importance. Then, the Internet and social media gave organizations the opportunity to have a global presence, something that dramatically increased their international audience. The so-called Social Media added another dimension to the customer-business relationship which became more interactive but also created more freedom for customers. This subsequently evolved into a part of brand marketing strategy worldwide, with sponsorship as perhaps the most probable avenue to create two-way relationships between the consumer and the brand. Besides their promotional material in thousands of brand logos can virtually be seen in almost every sports facility and sport equipment, but also in the names of basketball arenas and team-shirts. Sport Sponsorship is linked to consumer behavior variables and brand enhancers resulting in high fan engagement, namely performance tolerance where people do not mind if the sponsored brand performs badly; and brand basking where people takes pride in the competitive performance of his preferred sport team. A whole spectrum of other relevant dimensions of customer engagement include watching sports as a social attraction, being part of a memorable festive marketing event, exchanging dialogue about the sponsored sport team and finally, discussing a brand through speech with friends and peers. Customer engagement and brand attitude have been studied together in more recent years, but most importantly customer engagement and sponsorship activation (as ambient sport marketing) has not yet been linked as much as it should, most importantly in a social media context. Therefore, this paper effectively provides enhanced knowledge on the particulars of this study, which are the customer engagement in sports and in sport sponsorship and dimensions that may enhance brands. Furthermore, social media benefits acquired from sponsorship activation are also discussed. Taking 666 consumers of sports as part of our respondents beside other 4 cases of 2 sponsorship dyads among others by following a MMR methodology is far greater than what has been previously written and the results have shown that sponsorship activation usage acts accelerator to to the factors of engagement of sport fans through social media platforms, and brand enhancement is significantly linked with the level of usage of sponsorship activation in brand marketing and the level of customer engagement. Valuable insights from the sponsorship partners’ mechanisms and characteristics and their sport sponsorship-related performance for reinforcing fans involvement and brand enhancement behind the quantitative results are identified, complementing each other.
ΕΝΕΡΓΟΠΟΙΗΣΗ ΑΘΛΗΤΙΚΗΣ ΧΟΡΗΓΙΑΣ ΓΙΑ ΠΕΛΑΤΕΙΑΚΗ ΔΕΣΜΕΥΣΗ ΚΑΙ ΕΠΙΔΡΑΣΗ ΤΗΣ ΣΤΗ ΔΥΝΑΜΗ ΚΑΙ ΣΤΗΝ ΥΠΕΡΑΞΙΑ ΤΗΣ ΜΑΡΚΑΣ ΜΕΣΩ ΤΩΝ ΜΕΣΩΝ ΚΟΙΝΩΝΙΚΗΣ ΔΙΚΤΥΩΣΗΣ
Keywords: Αθλητισμός - Μάρκετινγκ; Μέσα κοινωνικής δικτύωσης; Ηλεκτρονικά κοινωνικά δίκτυα; Αθλητική χορηγία; Ονομασία προϊόντων - Μάρκετινγκ; Sports - Marketing; Social media; Online social networks; Sports sponsorship; Branding (Marketing); Sponsorship activation; Customer engagement; Branding; Social media